Anti-inflammatory effect of elemental diets with different fat composition in experimental colitis. Issue 7 (14th April 2014) - Papada, E.; Kaliora, A. C.; Gioxari, A.; Papalois, A.; Forbes, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of the present study was to evaluate the effectiveness of two isoenergetic elemental formulae with different fat content in the rat model of trinitrobenzene sulphonic acid (TNBS) colitis that mimics human inflammatory bowel disease. A total of forty-five male Wistar rats were assigned to five groups: (1) control group; (2) TNBS-induced colitis group; (3) TNBS-induced colitis group fed a long-chain TAG (LCT)-rich diet; (4) TNBS-induced colitis group fed a medium-chain TAG (MCT)-rich diet; (5) TNBS-induced colitis group fed a baseline diet and administered infliximab. Nutritional management lasted 12 d before and 4 d after rectal administration of TNBS. Subsequently, the rats were killed, and colonic tissue samples were collected for the assessment of histology, inflammation and oxidative stress. The MCT-rich diet decreased IL-6, IL-8 and intercellular adhesion molecule-1 (ICAM-1) levels and glutathione S-transferase (GST) activity, while the LCT-rich diet reduced only ICAM-1 levels and GST activity (P< 0·05). Neither elemental formula affected IL-10 levels. Infliximab reduced IL-8 and ICAM-1 levels and GST activity and increased IL-10 levels (P< 0·05). No significant differences were detected in oxidative stress. Histological damage scores differed significantly only between the control and the TNBS-induced colitis group. A MCT-rich formula seems to exert stronger anti-inflammatory effects than a LCT-rich formula in TNBS colitis.